Predella z przedstawieniem Pokłonu Trzech Króli. Zagadnienie pierwowzorów graficznych warsztatu tryptyku z Szamotuł. Ze zbiorów Muzeum Archidiecezjalnego w Poznaniu - Woźniak-Raciborska, Monika (Ecclesia. Studia z Dziejów Wielkopolski, 2018)
The focus of the study is the relation between the representation of the „Adoration of the Magi” from the Triptych from Szamotuły (housed at the Archdiocesan Museum in Poznań) to a wood engraving by Hans Süss von Kulmbach. The author shows the differences and similarities between the predella from Szamotuły and the wood engraving. She also argues that the workshop of the Triptych from Szamotuły was a prototype for other works such as the triptych from Szamotuły (1521), the painting „St. Anne with the Virgin and the Child and with St. Andrew and St. Jerome” (ca. 1521), the triptych from Mądre (1529), the painting of Our Lady from Gostyń (1540), the painting of Our Lady from Krobia (1542)).